The Role of Islamic Education in Promoting Environmental Awareness and Sustainable Economic Behavior Among Youth - Ismaul Fitroh; Heri Usodo; Ma. Criselda Robles (Green Economics: International Journal of Islamic and Economic Education, 2024)
This study investigates the impact of Islamic education on promoting environmental awareness and sustainable economic behavior among youth. As environmental issues continue to pose significant global challenges, fostering eco-conscious behavior among the younger generation is essential for ensuring long-term sustainability. Islamic education, with its emphasis on ethical responsibility, stewardship, and accountability as outlined in the Quran and Hadith, provides a unique framework for shaping pro-environmental attitudes and behaviors. This experimental study compares two groups of students: the treatment group exposed to green-Islamic content and the control group receiving general civic education. The research measures students' environmental awareness, knowledge of sustainability, and behavior before and after the intervention, using pre-test and post-test questionnaires, as well as qualitative interviews. The results indicate that the treatment group exhibited a significantly greater improvement in environmental awareness and sustainable behavior compared to the control group. These findings suggest that Islamic education, by integrating religious and ethical principles into environmental education, can effectively encourage sustainable behaviors such as resource conservation, waste management, and ethical consumption. The study highlights the importance of incorporating Islamic values into educational curricula as a means to foster a more environmentally responsible generation. Additionally, the research emphasizes the need for further studies to explore the long-term effects of eco-conscious Islamic education across different cultural and educational contexts. The results of this study contribute to the growing body of knowledge on the role of religious education in addressing global environmental challenges and promoting sustainable development.